Nuevas adiciones al conocimiento de las macroalgas marinas de la isla de Alborán (Mediterráneo Occidental) - Conde, Francisco; Flores-Moya, Antonio (Acta Botanica Malacitana, 2000)
Nuevas adiciones al conocimiento de las macroalgas marinas de la isla de Alborán (Mediterráneo Occidental)